First person - Ralitsa Madsen (The Company of Biologists, 2021)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Ralitsa Madsen is first author on 'NODAL/TGFβ signalling mediates the self-sustained stemness induced by PIK3CAH1047R homozygosity in pluripotent stem cells', published in DMM. Ralitsa conducted the research described in this article while a member of Prof. Robert Semple's lab, initially as a PhD student at the Wellcome Trust-Medical Research Council Institute of Metabolic Science-Metabolic Research Laboratories at Addenbrooke's Hospital, University of Cambridge, UK, and then as a Postdoctoral Research Fellow at the University of Edinburgh, UK. She is now a Sir Henry Wellcome Postdoctoral Fellow in the lab of Prof. Bart Vanhaesebroeck at University College London Cancer Institute, London, UK, investigating the cellular context-dependent PI3K signalling code, and its reprogramming in human disorders such as cancer and benign overgrowth.